The 3-3-1 Models in Current Particle Physics - Dong, Phung Van (Communications in Physics, 2014)
We review the main contribution of the Division for Theoretical Particle Physics at the  Institute ofPhysics, VAST  in building the models based on \(\text{SU}(3)_C\otimes \text{SU}(3)_L \otimes \text{U}(1)_X\)  gauge unification